Ubiquitous database in mobile healthcare - Zainal, Anazida; Kamat, Maznah; Kadir, Rashidah; Mat Din, Mazura (Faculty of Computer Science and Information System, 2005)
Ubiquitous Database in Mobile Healthcare (UDMHC) in Emergency Handling System is utilizing the combined benefit of smart card to support mobility coupled with the ubiquitous access of distributed database via web technology, in order to promote a truly mobile and interactive medical information technology. UDMHC provides benefits of storing comprehensive, accurate and up to date medical information while offering the ease of mobility in pocket. In the time of accident or emergency, UDMHC provides medical-related professional the best solution in immediately retrieving accurate, concise and vital victims medical record, allergies, and other information necessary for medical treatment decisions. Applet provides flexibility in retrieving the users information, users medical information and emergency contact list from ubiquitous database in the smart card. It also provides interaction with other distributed hospital database via HTTP protocol in order to retrieve the victims detail information. This provides a convenient way to gather, adapt, and share data from different hospital. Result indicated that network environment is able to be spanned across hospital, clinic and country boundaries, hence provides better ubiquitous medical record management. The Internet technology offers the opportunity for distributed health services to exchange medical knowledge and allow dynamic monitoring of patients health. With the deployment of Java and open card technology, UDMHC can be seamlessly and ubiquitously applied in any platform.